2015
DOI: 10.1007/s12350-014-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center assessment of the temporal trends in myocardial perfusion imaging

Abstract: There has been a temporal decline in the prevalence of abnormal and ischemic MPI studies as well as the frequency and extent of obstructive CAD on angiography. However, this decline was not to the same extent as previously reported, and the overall 34% abnormal MPI rate, with 19% in patients with no known CAD and 65% in patients with known CAD, remains a clinically relevant percentage of patients tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 21 publications
5
34
0
Order By: Relevance
“…5 The population of coronary disease patients has grown over the past two decades and a greater percentage of patients now studied by nuclear stress testing are those with known coronary artery disease than in the past. 2 The Duval study also confirms that there has been a particularly big drop in the number of patients with severe ischemia. This likely reflects larger trends in how our patients are managed, their outcomes, and public knowledge about heart disease.…”
Section: See Related Article Pp 539-551mentioning
confidence: 74%
See 1 more Smart Citation
“…5 The population of coronary disease patients has grown over the past two decades and a greater percentage of patients now studied by nuclear stress testing are those with known coronary artery disease than in the past. 2 The Duval study also confirms that there has been a particularly big drop in the number of patients with severe ischemia. This likely reflects larger trends in how our patients are managed, their outcomes, and public knowledge about heart disease.…”
Section: See Related Article Pp 539-551mentioning
confidence: 74%
“…The frequency of angiographic one vessel and multivessel coronary artery disease has shown similar decreases in the author's institutions cardiac catheterization laboratories as well. 2 Although there are several potential explanations for these finding, (i.e., changing referral patterns and improved camera technology) the data taken together particularly support the conclusion that the burden of coronary atherosclerotic disease is less than it used to be.…”
Section: See Related Article Pp 539-551mentioning
confidence: 93%
“…16,17 In a study by Rozanski et al of 39,515 patients with no history of CAD that underwent diagnostic stress MPI from 1991 to 2009, the prevalence of normal MPI studies was noted to have increased among all subgroups from a prevalence rate of 59.1% in 1991, to 91.3% in 2009. 16 In a recent multicenter study of 108,654 patients undergoing clinically indicated stress MPI studies, an overall increase in the prevalence of normal studies was seen from 1996 to 2012 in all patients (46.2% to 68.2%), patients without CAD (67.8% to 82%), and patients with CAD (25.3% to 39.2%).…”
mentioning
confidence: 99%
“…16 In a recent multicenter study of 108,654 patients undergoing clinically indicated stress MPI studies, an overall increase in the prevalence of normal studies was seen from 1996 to 2012 in all patients (46.2% to 68.2%), patients without CAD (67.8% to 82%), and patients with CAD (25.3% to 39.2%). 17 If only half of the patients who undergo a stress-first protocol are normal and do not undergo rest imaging, the ASNC goal could be met solely by converting a laboratory to a stress-first approach instead of the standard rest-stress structure of most nuclear laboratories.…”
mentioning
confidence: 99%
“…First, it may be related to the downtrend in the burden of myocardial ischemia and coronary disease burden which has been reported in recent literature. 7,8 Second, this observation may be due to MPI testing of lower risk population over the years, coinciding with the switch from adenosine to regadenoson. Testing a lower risk population may be directly related to the switch to regadenoson.…”
mentioning
confidence: 99%